The Long and Short of It: Mahā-vākya from Mīmāṁsā to Jīva Gosvāmin, from the Veda to the Bhāgavata. (19th July 2018) - Uskokov, Aleksandar
Abstract: In this article, I focus on the idea of mahā-vākya in the theology of Jīva Gosvāmin. I show how Jīva drew on two distinct understandings of mahā-vākya, those of Mīmāṁsā and Advaita Vedānta, to claim that: (1) the whole Veda, including the Itihāsa-Purāṇa corpus, was one large mahā-vākya; (2) a quarter verse from the Bhāgavata was a mahā-vākya; (3) the praṇava Oṁ was a mahā-vākya . I argue that Jīva used the notion of mahā-vākya to show that all the Vedas, epics, and Purāṇas denote Kṛṣṇa through the fact that the single most important scriptural statement, 'Kṛṣṇa is the Supreme Lord' of Bhāgavata Purāṇa 1.3.28, has Kṛṣṇa as its reference. I conclude that mahā-vākya for Jīva was just a tool that he used for the purpose of canon formation in which the central role would belong to the Bhāgavata.